Program of fragmentary revitalization of the historical town of Lyashky Murovani.: Murovane Village, Staryi Sambir district, Lviv Region - Lukomska, Zoriana; Shevchuk, Iryna; Lukomska, Halyna (Budownictwo i Architektura / Civil and Architectural Engineering, 2020)
The research uncovers the value and uniqueness of the volumetric planning structure of the historical town of Lyashky Murovani, now known as Murovane Village, Staryi Sambir district in the Lviv region. Within the town features of Baroque urban planning are found and characteristics of the historical urban development of the location are revealed. The current components of the volumetric and spatial composition of the former city are analysed. A reconstruction scheme of the 17th-century city planning structure was presented, when it consisted of a market square with residential buildings blocks, sacral objects, and a palace and park complex. The study also reveals that the urban object passed through several stages of reconstruction during its development. A fragmentary revitalization program of the historical town into a modern village of Murovane was proposed.